2014
DOI: 10.1007/s00726-014-1818-8
|View full text |Cite
|
Sign up to set email alerts
|

Linking our understanding of mammary gland metabolism to amino acid nutrition

Abstract: Amino acids (AA) are not only building blocks of protein but are also key regulators of metabolic pathways in animals. Understanding the fate of AA is crucial to optimize utilization of AA for milk protein synthesis and, therefore, to reduce inefficiencies of nutrient utilization during lactation. By understanding the functional role of AA metabolism in mammary tissue, we can uncover pathways and molecular targets to improve AA utilization by mothers and neonates during the lactation period. The major objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 179 publications
0
62
0
Order By: Relevance
“…For example, SLC27A1 transports cationic L-AA (His, Arg, and Lys; Closs et al, 2006). The SLC38A1 and SLC38A2 transport neutral-AA such as Ala, Ser, Gly, Pro, Cys, and Gln (Mackenzie and Erickson, 2004;Manjarin et al, 2014). The abundance of SLC7A1, SLC38A1, and SLC38A2 along with CSN1S1 was upregulated in response to enhanced Met supply (P ≤ 0.03; Table 4).…”
Section: Resultsmentioning
confidence: 98%
“…For example, SLC27A1 transports cationic L-AA (His, Arg, and Lys; Closs et al, 2006). The SLC38A1 and SLC38A2 transport neutral-AA such as Ala, Ser, Gly, Pro, Cys, and Gln (Mackenzie and Erickson, 2004;Manjarin et al, 2014). The abundance of SLC7A1, SLC38A1, and SLC38A2 along with CSN1S1 was upregulated in response to enhanced Met supply (P ≤ 0.03; Table 4).…”
Section: Resultsmentioning
confidence: 98%
“…Free amino acids in blood enter into mammary cells by amino acid transport systems with respective transporters for different groups of amino acids (90, 94). After the uptake of amino acids from blood, the basic process for protein synthesis in the mammary gland is similar to that in other tissues.…”
Section: Originsmentioning
confidence: 99%
“…A recent study reported that exogenous growth hormone can increase milk protein synthesis . Additionally, numerous studies in mice and cows have demonstrated that amino acids (AA), such as Leu, Ile, Met, and Thr, act as signaling molecules to regulate milk synthesis and lactation . The mammalian target of rapamycin (mTOR) pathway participates in milk protein synthesis.…”
Section: Introductionmentioning
confidence: 99%